Exploring Self-Potential Through Guidance and Counseling Services: Success Towards the Future - Khotimah, Husnul (Lembaga Bale Literasi, 2023)
This study shows that tutoring services (BK) are essential in helping people discover their potential and achieve success in the future. The main aim of the study was to find out how counseling sessions can help people understand themselves, set goals, develop skills, and overcome various challenges to improve their future. The research conducted a thorough analysis of the scientific literature on the role of BK in developing self-potential and achieving success. The results showed that BK greatly helps people in self-understanding, setting achievable goals, and developing the skills necessary to achieve success in various aspects of life. This research can provide an in-depth picture of how BK services can help people maximize their potential.